Nutritional Qualities Of Hilsha And Sarpunti In Different Salt Curing Methods - Mustafa, Md Ghulam; Begum, Sayeda Rezwana; Khaleque, Md Abdul; Jannat, Meshkatul; Ahsan, Dewan Ali (Dhaka University Journal of Biological Sciences, 2012)
Qualities of different salt curing methods such as pickle, mixed, dry and brine salting were assessed in respect of biochemical composition in hilsha and sarpunti. In hilsha, protein, fat and calcium (Ca) contents were slightly higher in laboratory salted products than that of commercial one and phosphorous (P) and iron (Fe) were more or less similar in both laboratory and commercial cases. In sarpunti protein, fat, P and Fe contents were more or less similar both in laboratory and commercially salted products but Ca content is significantly higher in four types of laboratory products than those of commercial one. Among the four salted products of hilsha and sarpunti, the protein (36.24 ± 0.58 and 34.04 ± 0.62%), fat (6.81 ± 0.34 and 11.34 ± 0.60%), Ca (114.45 ± 1.45 and 444.13 ± 0.83 mg/100g fish), P (193 ± 1.40 and 124.09 ± 1.37 mg/100g fish) and Fe (1.37 ± 0.13 and 2.19 ± 0.27 mg/100g fish) were found. Contents were the highest in mixed salted products. Moreover, for producing the finished products dry salting required the least time (5 days in hilsha and 10 days in sarpunti). However, on the basis of the quality and performance, the suitability of four salting methods can be arranged as follows: mixed > dry > pickle > brine. DOI: http://dx.doi.org/10.3329/dujbs.v21i1.9749 DUJBS 2012 21(1): 97-104